Paper Printing Services Signboards around Campus Building (A Case of Multimodal Linguistic Landscape) (e-Journal of Linguistics, 2023)
Micro, Small and Medium Enterprises are currently becoming one ofthe concerns and priorities of the Indonesian government. Every Micro,Small and Medium Enterprises (MSME) actor builds a business in alocation that is considered to have the potential to generate profits. Onetype of MSME is a paper printing services. This research is a case studyof landscape linguistics with a multimodal approach. This study aims toanalyze the representation meaning, interactional meaning andcompositional meaning of outdoor signs on paper printing businesssignboards at the Unika Santu Paulus Ruteng campus buildingsurrounding; in the east, south and west of the campus building. Theresults showed that all outdoor sign data on the signage were verbalsigns supported by several contrasting color backgrounds. Therepresentation meaning of the signboards represents the type ofbusiness being run, namely the paper printing services. It is indicated bythe two main keywords that appear on every signboard, including theword “print or printing” and “photocopy/copi”. In the aspect ofcompositional meaning, all the data on the signboards containsinformative value. Information is placed in a non-linear text framingposition and is not placed sequentially. In the salience aspect, the verbalsign in the form of the business name is placed at the top position and isthe most salience element in the sign. Placement and a more salienceverbal signs aim to make it easier for viewers to see the place ofbusiness as well as show the identity and type of business being run. Onthe other hand, the use of abbreviations on the signboards of a “startupbusiness” creates confusion if it is not accompanied by clear additionalinformation.
Keywords: paper printing services; signboards; multimodal analysis; linguistic landscape